HUBUNGAN FORENSIK AUDIT, SINGLE IDENTITY NUMBER, MONEY LAUNDRY DAN KORUPSI - Heridiansyahj, Jefri; Warno, Warno (JURNAL STIE SEMARANG, 2009)
Mass media mention that result of international transparency survey of  Indonesia to 900 company mention that 40% up to 60% acceptance  of corruption  lease  by government  officer,  even  this  state  enter  ranking  of corrupt state top three in the world, besides the state represent its heaven of money laundry. As according to System Management Bases data theory or of DBMS (  Database   Management   of  System)  is  software   to  define,   creating, managing and controling accessing of basisdata. DBMS is data aggregate which is program corps and interaction for data access, so SIN through to be   able  to  trace  every  information  of  individual  activity  in  this  country, because have integrated, with existence of DBMS hence in making an audit of ( Forensic Audit) in order to to know the existence of money laundry and corruption can be easier, because every data needed can be obtained that thing is because the information have been saved in data base